Elaboration of a food mixture based on quinoa (Chenopodium quinoa Willd), cañihua (Chenopodium pallidicaule Aellen), barley (Hordeum vulgare L.), corn (Zea mays L.), bean (Vicia faba L.) and soybean (Glycine max L Merr) by cooking-extrusion process - Aro Aro, Juan Marcos (2019)
The research aims to formulate a food mixture based on quinoa, cañihua, barley, corn, beans and soy using cooking-extrusion technology. The optimal mixture was made with formulations of better chemical computation, the mixture containing 28.8% pearl quinoa, 9.25% cañihua, 5.00% barley, 6.00% bean, 3.00% corn, 8.00% soybeans, 29.50% being favored of sugar, 8.00% of vegetable oil, 0.20% of essence, 2.00% of tricalcium phosphate and 0.25% of vitamins. The mixture was subjected to the extrusion cooking process using 15% humidity, 180° C temperature and 457 rpm, obtaining a gelatinization index 98.30% considering a good cooking index of the instant mixture. The functional characteristics of the selected instant mixture were evaluated obtaining, absorption index with 6.1%, solubility index with 19.8%, expansion index with 1.64 cm and nitrogen solubility index with 35%. The quality of the instant mix protein indicated that it is a very good quality protein since, in relation to milk casein, the apparent digestibility, true digestibility, net protein utilization and biological value were 90%, 78 % and 89%. The sensory tests were favorable for the taste and the smell and color were improved by means of flavorings and dyes in the instant mixture and the microbiological analyzes were accepted after 10 days of storage at room temperature. A useful life of 90 days is concluded.